Неологізація лексики в час пандемії коронавірусу (на матеріалі інтернет-видань та соціальних мереж) - Красавіна, В. (Культура слова, 2020)
У статті висвітлено неологізаційні процеси в лексичному складі сучасної української літературної мови. Проаналізовано причини виникнення новацій й основні шляхи поповнення лексичного фонду неологізмами, зокрема внаслідок запозичень з інших мов, шляхом словотворення та модифікації семантичного значення. Схарактеризовано структурні, семантичні та функціональні особливості нових слів у медіатекстах. Having spread around the world, the Covid-19 pandemic has caused an increase in the number of neologisms both in Ukrainian and in other languages. In the first place, it happened due to extralinguistic factors – specific features of the infectious disease itself as well as the unprecedented social practices which have become a new method of adaptation to the present day circumstances. Language has promptly reacted to large-scale changes in the world and the society: new words and word combinations denoting the phenomena, objects and notions unknown before have appeared; the modification of the semantics of certain common words has taken place; the sphere of usage of some specialized terms has broadened. Globalization processes and a tendency towards language unification have facilitated the spread of terms of international use, neolexemes, neomorphemes, which is indicative of the emergence of the common international vocabulary. English borrowings have been actively adopted due to the language practice of mass media (in particular, the electronic ones), which are dynamic and open to innovation, and, as is the case with social networks, enable the communication of a great number of people of various nationalities, ages and social status. Thus, neologisms are social markers of transformations, typical of the society in a globalized world. Renovation of the vocabulary is happening by means of adoption of foreignisms, predominantly of the English origin, international terms, which are replenishing terminology subsystems, in particular the ones of healthcare and administration, etc.; by means of word-formation using borrowed derivation tools; due to the activation of the processes of extending the semantics of already familiar words. A considerable amount of new words will not enter the general vocabulary as upon the conclusion of the Covid-19 pandemic they will be excluded from the active use and transferred to the corpus of historical words of the epoch which will become the evidence of the period of the quarantine measures and self-isolation of the citizens, and some words will be returned to a specialized sphere of use.